Application of the Baylis-Hillman reaction in the preparation of quinoline derivatives - Pakade, Vusumzi Emmanuel (Rhodes University, Faculty of Science, Department of Chemistry, 2006)
The reaction of various 2-nitrobenzaldehyde derivatives with methyl vinyl ketone (MVK) in the presence of 1,4-diazabicyclo[2.2.2]octane (DABCO) has afforded the Baylis-Hillman adducts in moderate to good yield. Dissolution of the catalyst in the solvent before the addition of the aldehyde was observed to improve the yield. Reduction of the Baylis-Hillman adducts was effected by catalytic hydrogenation using a 10% palladium-on- carbon catalyst in ethanol to give quinoline and quinoline-N-oxide derivatives and, in some cases, acyclic reduction products. All products were characterised using NMR and, where appropriate, HRMS methods. Selected quinoline-N-oxides were successfully converted to their corresponding quinoline derivatives using phosphorus tribromide (PBr₃) and DMF as solvent. Conjugate addition of the benzylamine and piperidine nucleophiles to the Baylis-Hillman adducts was also investigated but proved problematic, with one of the substrates undergoing a retro-Baylis-Hillman reaction to afford the aldehyde in ca. 40% yield, but seemingly only traces of the required product. Perkin-type coupling of two 2-methylquinolines with benzaldehyde was successfully effected to afford the desired styrylquinoline derivatives confirming the potential of the Baylis-Hillman approach to the construction of the analogues of known HIV-1 integrase inhibitors. Three ¹³C NMR chemical shift prediction programmes, viz., Chem Window, neural network and HOSE (hierarchically ordered spherical description of environment) methods were applied to selected representative compounds prepared in the project. The results from the three programmes correlated reasonably well with the experimental carbon-13 chemical shift data for each of the selected compounds.
Keywords: Heterocyclic compounds -- Derivatives; Quinoline